17. CHANGES IN CENTRAL CORNEAL THICKNESS AFTER SMILE SURGERY (Vietnam Journal of Community Medicine, 2023)
Purpose: To compare central corneal thickness before and after SMILE surgery. Methods: A prospective study, the clinical description was conducted on 40 eyes (21 patients) with myopic and myopic astigmatism who had been studied by Smile surgery. Central corneal thickness measurements were performed preoperatively, 1 week, 1 month, 3 months, 6 months postoperatively. Results: 52% male and 48% female, with a mean age of 23.18 ± 4.14 years, were analyzed. The spherical equivalents were -6.41±1.67 (ranging from -1.50D to – 9.75D). The mean central corneal thickness before surgery was 545.48±27,85 µm. It significantly decreased to 436.65 ± 33.83µm at 1 week, the increased to 441.73 ± 33.04 µm at 1 month, kept on increasing to 444.00 ± 32.58 µm at 3 months and became stable 6 months after surgery. Conclusion: Mean central corneal thickness decreased after Smile surgery and later increased from 1 month to 3 months, then stable 6 months after surgery.
Keywords: Corneal thickness, SMILE.